Drought levels of several soybean's variety (Glycine Max L. Merril). Issue 1 (April 2020) - Aminah,; Palad, Marliana S; Sahur, Asmiaty
Abstract: Demand for soybeans in Indonesia is very high however, the domestic production is not sufficient enough for the community's needs for soybeans so it must be fulfilled through imports. The slow rate of soybean's production improvement in Indonesia caused by national low productivity that only reaches 1.30 tons/ha. While the potential increase in national soybeans can reach 2.2 million tons/ha. This research aims to find out some soybean varieties that are tolerant and sensitive to drought stress. This research was carried out at the Green House Cereals Plant Hall in Maros Regency, which began in July to October 2018. This research used factorial Randomized Group Design (RGD), Factor I is a soybean variety (V), consists of 4 varieties, namely : V1 = Tanggamus (tolerant to drought stress), V2 = Wilis variety (tolerant to drought stress), V3 = Anjasmoro variety (sensitive to drought stress), V4 = Argomulyo variety (sensitive to drought stress). The second factor is drought stress level (K) consists of 3 levels, namely: K1 = 80% field capacity, K2 = 60% field capacity, K3 = 40% field capacity. The results obtained that there is a decrease in all characters of the seed yield up to 50% along with the decrease in availability of groundwater in all tested varieties. The Tanggamus variety as a tolerant variety is still able to maintain several characters better than the other three varieties at 40% water availability, namely the number of pods, root length and stomata density. There are interactions between several soybean varieties and the level of drought stress on observations of plant growth and observation.